Hezbollah’s transnationalities between terrorism and organized crime. The case of the “Triple Frontera” (Rivista di Studi e Ricerche sulla criminalità organizzata, 2023)
The article addresses the relationship between terrorism and organized crime by focusing on the case of the Hezbollah group. By reconstructing the illicit activities – drug trafficking and money laundering – developed through the network of militants present in South America, the article highlights the role of the Triple Frontera, or Triborder area, border and free trade area (since 1970) between Paraguay, Argentina and Brazil.
Keywords: Hezbollah; Triple Frontera; organized crime; Southern America; terrorism